2012
DOI: 10.1210/en.2012-1750
|View full text |Cite
|
Sign up to set email alerts
|

Additive Effects of Nicotine and High-Fat Diet on Hepatic Steatosis in Male Mice

Abstract: Smoking is a major risk factor for diabetes and cardiovascular disease and may contribute to nonalcoholic fatty liver disease. We hypothesize that in the presence of nicotine, high-fat diet (HFD) causes more severe hepatic steatosis in obese mice. Adult C57BL6 male mice were fed a normal chow diet or HFD and received twice daily injections of nicotine (0.75 mg/kg body weight, ip) or saline for 10 wk. Light microscopic image analysis revealed significantly higher lipid accumulation in livers from mice on HFD pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
87
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 56 publications
(99 citation statements)
references
References 61 publications
12
87
0
Order By: Relevance
“…The apoptotic nature of the cell death and the identity of the dying cardiomyocyte were further confirmed by electron microscopy (Friedman et al 2012; Sinha-Hikim et al 2011a, 2014). Enumeration of TUNEL-positive (apoptotic) and TUNEL-negative (non-apoptotic) nuclei was carried out in left ventricular sections stained with the ApopTag peroxidase kit by using an American Optical Microscope with a ×40 objective and a pair of ×10 eyepieces.…”
Section: Methodsmentioning
confidence: 76%
See 3 more Smart Citations
“…The apoptotic nature of the cell death and the identity of the dying cardiomyocyte were further confirmed by electron microscopy (Friedman et al 2012; Sinha-Hikim et al 2011a, 2014). Enumeration of TUNEL-positive (apoptotic) and TUNEL-negative (non-apoptotic) nuclei was carried out in left ventricular sections stained with the ApopTag peroxidase kit by using an American Optical Microscope with a ×40 objective and a pair of ×10 eyepieces.…”
Section: Methodsmentioning
confidence: 76%
“…Mice on either diet ( n = 5) received twice-daily intraperitoneal (IP) injections of nicotine (0.75 mg/kg body weight [BW]) or saline for 16 weeks. The rationale for using twice daily IP administration of nicotine (0.75 mg/kg BW) was based on the results of our previous studies, which demonstrated that this dose level of nicotine, when combined with HFD, triggered greater oxidative stress, activated hepatocellular apoptosis, amplified HFD-induced hepatic steatosis (Friedman et al 2012) and caused intramyocellular lipid accumulation and intramyofibrillar mitochondrial abnormalities in the skeletal muscle (Sinha-Hikim et al 2014). Notably, the daily dosage of 1.5 mg/kg BW in mice appeared to be similar to the clinically relevant concentrations found in habitual cigarette smokers and users of nicotine-containing chewing gum (Wu et al 2015).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, chronic inhalation of low levels of ambient air particulate matter (PM 2.5) has been was reported to induce hepatic steatosis and lipid peroxidation and, moreover, increase hepatic inflammatory and fibrosis stage in mice (Tomaru et al 2007, Tan et al 2009). Exposure to nitrosamines and nicotine has also been found to play critical roles in the pathogenesis of NAFLD (Tong et al 2009, Azzalini et al 2010, Friedman et al 2012.…”
Section: Introductionmentioning
confidence: 99%